Calcium dobesilate efficiency in the treatment of diabetic kidney disease through suppressing MAPK and chemokine signaling pathways based on clinical evaluation and network pharmacology - Du, Bingyu; Yin, Yanyan; Wang, Yuqing; Fu, Hui; Sun, Helin; Yue, Zhaodi; Yu, Shaohong; Zhang, Zhongwen (Frontiers in Pharmacology, 2022)
Aims: To evaluate the effectiveness and potential mechanism of Calcium Dobesilate (CaD) in pa-tients with diabetic kidney disease (DKD). Methods: We searched for available randomized con-trolled studies about DKD patients’ treatment with CaD through open databases. Continuous varia-bles were expressed as standardized mean difference (SMD) with a 95% confidence interval (CI). The putative targets and possible pathways of CaD on DKD were analyzed by network pharmacolo-gy. Molecular docking was employed to verify the matching between CaD and the target genes. Results: In the meta-analysis, 42 trials were included, involving 3671 DKD patients, of which 1839 received CaD treatment in addition to conventional treatment, while 1832 received conventional treatment. Compared with routine therapy, the levels of serum creatinine (Scr) and blood urea nitro-gen (BUN) significantly decreased in the CaD treatment (early stage of DKD, Scr: P < 0.00001; BUN: P < 0.0001; clinical stage of DKD, Scr: P < 0.00001; BUN: P < 0.00001; kidney failure stage, Scr: P = 0.001; BUN: P = 0.004). The levels of serum cystatin C (Cys-C), urine levels of molecules reflecting kidney function (urinary albumin excretion rate (UAER) and micro glycoprotein) and in-flammatory factors (hypersensitive c-reactive protein (hs-CRP)) were reduced compared with con-trol groups, while glomerular filtration rate (GFR) was increased in patients treated with CaD for 12 weeks. CaD also showed a better effect on improving endothelial function. Network pharmacology results showed that the interaction pathway between CaD and DKD is mainly enriched in MAPK and chemokine signalling pathway. AKT1, CASP3, IGF1, MAPK8 and CCL5 might be the key tar-gets for CaD in the treatment of DKD. Conclusions: Combination with CaD is effective and safe in patients with DKD. Inhibition of MAPK and chemokine signalling pathways might play a vital role in treating CaD in DKD patients.